Wetting of YSZ by molten Sn–8Zr, Sn–4Zr–4Ti, and Sn–8Ti alloys at 800–900 °C. Issue 1 (1st January 2022) - Lin, Qiaoli; Tan, Kaihui; Wang, Le; Sui, Ran
Abstract: The wetting of 3% yttria-stabilized zirconia (YSZ) by Sn–8Zr, Sn–4Zr–4Ti, and Sn–8Ti alloys was studied at 800–900 °C. Both Zr and Ti improve the wettability via the formation of reaction products and adsorption. In the systems containing Zr additives in the alloys, ZrO2- x precipitates preferentially, and the wettability is dominated by interface adsorption. An anomalous temperature dependence was found in the final wettability of these systems owing to the decrease in adsorption with an increase in the temperature. The spreading dynamics are controlled by the dissolution of Zr, followed by the formation of a wetting ridge. The wettability of the Sn–8Ti/YSZ system is dominated by the precipitation of reaction products (Ti2 O3 and Ti11.31 Sn3 O10 ). The reaction kinetics is the limiting factor for spreading in Sn–8Ti/YSZ, and the adsorption at the interface significantly decreased the energy barrier for wetting.